2007
DOI: 10.1002/app.26071
|View full text |Cite
|
Sign up to set email alerts
|

Microcellular foaming of PE/PP blends

Abstract: Three different polyethylene/polypropylene (PE/PP) blends were microcellular foamed and their crystallinities and melt strengths were investigated. The relationship between crystallinity, melt strength, and cellular structure was studied. Experimental results showed that the three blends had similar variation patterns in respect of crystallinity, melt strength, and cellular structure, and these variation patterns were correlative for each blend. For all blends, the melt strength and PP melting point initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…Apart from the basic foaming conditions (temperature, pressure et al), composition of the blends as well as other additives could affect the material properties (such as crystallinity, 18 surface tension, 19,20 melt strength, [21][22][23] solubility and diffusivity of CO 2 24 ) and ultimately determine the foam morphology and properties. [25][26][27][28][29][30][31] For example, Rachtanapun et al 32 have found that PP/HDPE ¼ 30/70 blends, prepared by twin screw extruder at 100 rpm using CO 2 as blowing agent, exhibit poor foam morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the basic foaming conditions (temperature, pressure et al), composition of the blends as well as other additives could affect the material properties (such as crystallinity, 18 surface tension, 19,20 melt strength, [21][22][23] solubility and diffusivity of CO 2 24 ) and ultimately determine the foam morphology and properties. [25][26][27][28][29][30][31] For example, Rachtanapun et al 32 have found that PP/HDPE ¼ 30/70 blends, prepared by twin screw extruder at 100 rpm using CO 2 as blowing agent, exhibit poor foam morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarized the weight ratios of PLA composites. A self-design batch-foaming setup was used in this study [14,15] . The carbon supercritical dioxide was used as blowing agent with a continuous gas pressure of 15 MPa.…”
Section: Composites Preparationmentioning
confidence: 99%
“…[7][8][9][10][11] Rare earth elements have also been reported to be capable of modifying the primary Mg 2 Si particles. [12] Recently, P was added to the composite and the results show a great change in size and morphology of primary particles and a transition from flakes to fibers in the eutectic structure. [13] Assuming an analogy with the modification of Al-Si alloys by such elements as Na and Sr, a refinement of the microstructure is expected to result in an improvement of the mechanical properties.…”
Section: Introductionmentioning
confidence: 98%
“…So far the finest size of primary Mg 2 Si particle reported in the literature is about 8 lm. [12] The objective of the present study is to evaluate the tensile properties of Al-15 pct Mg 2 Si composites and fracture characteristics of the material with the addition of up to 0.3 pct Li.…”
Section: Introductionmentioning
confidence: 99%